The Effect Of Chemotherapy In Breast Cancer Patients On The Incidence Of Dry Eye - الشريقي فاتن; درويش تيم; عبدلله نادر (Latakia University Journal -Medical Sciences Series, 2024)
Objective: To study the signs and symptoms of dry eye in breast cancer patients before starting their chemotherapy an after four and eight cycles. Methods: 120 female patients attending the ophthalmology clinic at Tishreen University Hospital in Lattakia during the time period 2023-2024 participated in this observational study. The investigators included criteria for inclusion in the research, where a detailed medical history was taken, age and gender information was recorded, after obtaining informed consent and before the patient took any chemotherapy. A comprehensive ophthalmic examination was performed, which included examining the anterior sections of the eye using a slit lamp, performing the Schirmer test, and measuring the tear film breakdown time (BUT). After that, the participating patients were subjected to the OSDI questionnaire. We repeated the previous examinations and procedures after administering the fourth dose of chemotherapy treatment., as well as after giving the eighth dose of it. The time period between each dose was 21 days.. Results: In this study, we found that 12 patients (10%) of the included patients had meibomian glands dysfunctions after the fourth dose, and the number increased to 60 patients (50%) after the eighth dose. The occurrence of punctate epithelial erosions (PEE) was found in 18 patients (15%) after the eighth dose of treatment. The values of all the studied variables were affected by Schirmer 1 tear film break-up time (BUT) and the ocular surface disease index (OSDI), as they differed statistically significantly in patients before treatment and after taking the fourth dose and the eighth dose of it, as the mean value of the OSDI increased and the mean value of tear film breakdown time and Schirmer 1 decreased ,(P - value = 0.0001). Conclusion: On the basis of these results, we found that chemotherapy given to breast cancer patients causes dry eyes and significantly affects the patient’s quality of life, and the degree of dryness increases with the number of doses given.